In vivo engineering and transplantation of axially vascularized and epithelialized flaps in rats - Mayer, Simon Andreas; Thomas, Benjamin; Heuer, Miriam; Brune, Jan C.; Eras, Volker; Schuster, Kilian; Knoedler, Leonard; Schaefer, Rebecca Luisa; Thiele, Wilko; Sleeman, Jonathan P.; Dimmler, Arno; Heimel, Patrick; et al. (Tissue engineering, 2025)
The arteriovenous loop (AVL) model allows the in vivo engineering of axially vascularized flaps, the so-called AVL flaps. Although AVL flaps can be transplanted microsurgically to cover tissue defects, they lack an epithelial layer on the surface. Therefore, the objective of this study was to engineer axially vascularized AVL flaps with an accompanying epithelial layer for local defect reconstruction. In this study, AVLs were established in 20 male Lewis rats. Minimally invasive injection of keratinocytes onto the surface of the AVL flaps was performed on postoperative day (POD) 21. AVL flaps were explanted from 12 rats on POD 24 or POD 30, then the epithelium formed by the keratinocytes on the surface of the flaps was evaluated using immunofluorescence staining. In six other rats, the AVL flap was locally transposed to cover a critical defect in the rats’ leg on POD 30 and explanted for analysis on POD 40. In two control rats, sodium chloride was applied instead of keratinocytes. These control flaps were also transplanted on POD 30 and explanted on POD 40. Our results revealed that 3 days after keratinocyte application, a loose single-layered epithelium was observed histologically on the AVL flaps surface, whereas after 9 days, a multilayered and structured epithelium had grown. The epithelium on the transplanted AVL flaps showed its physiological differentiation when being exposed to an air–liquid interface. Histologically, a layered epithelium identical to the rats’ regular skin was formed. In the sodium chloride control group, no epithelium had been grown. This study clearly demonstrates that axially vascularized AVL flaps can be processed in the subcutaneous chamber by minimally invasive injection of keratinocytes. Thus, AVL flaps with an intact epithelial layer were engineered and could be successfully transplanted for local defect coverage in a small animal model.